2017
DOI: 10.1103/physrevb.96.125422
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the intermediate-band absorption properties of type-II GaSb/GaAs quantum-dot photovoltaics

Abstract: Quantum-dot (QD) intermediate-band (IB) materials are regarded as promising candidates for high-efficiency photovoltaics. The sequential two-step two-photon absorption processes that take place in these materials have been proposed to develop high-efficiency solar cells and infrared (IR) photodetectors. In this work, we experimentally and theoretically study the interrelation of the absorptivity with transitions of carriers to and from the IB in type II GaSb/GaAs QD devices. Our devices exhibit three optical b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 68 publications
0
26
0
2
Order By: Relevance
“…Using either epitaxial quantum dots (QDs) or impurities one can introduce such a band 3,4 . A two step-photon process occurs from the valence band (VB) to the IB and from IB to the conduction band (CB), ultimately increasing light absorption of the solar spectrum without compromising the open circuit voltage (VOC) of the device 5 . The proof of concept for an IBSC has been realized, and it has been shown that the short circuit current can be increased by the introduction of QDs 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Using either epitaxial quantum dots (QDs) or impurities one can introduce such a band 3,4 . A two step-photon process occurs from the valence band (VB) to the IB and from IB to the conduction band (CB), ultimately increasing light absorption of the solar spectrum without compromising the open circuit voltage (VOC) of the device 5 . The proof of concept for an IBSC has been realized, and it has been shown that the short circuit current can be increased by the introduction of QDs 6 .…”
Section: Introductionmentioning
confidence: 99%
“…When only irradiated by the 784-nm LD, quasi-Fermi level is single. When the additional IR light pumps electrons from the IB into the CB, quasi-Fermi levels of the IB and the CB start splitting, and, therefore, the adiabatic process of the two-step photoexcitation recovers the output voltage 38 . In order to demonstrate the voltage recovery effect caused by two-step photoexcitation, we investigated short-circuit current, J SC , and open-circuit voltage, V OC , under the irradiation of the both sources, the 784-nm LD and the additional IR light.…”
Section: Resultsmentioning
confidence: 99%
“…In the proposed work, materials and their thickness are chosen from the previously reported literature [22, 23]. The thickness and doping concentration of 1D quantum confined superlattice are taken from experimental reports [26, 27]. The InGaP/GaSb tandem cell is designed by incorporating GaAs QS layers with a total area of 4.0384 × 10 −8 cm 2 .…”
Section: Physical Modelling and Simulationmentioning
confidence: 99%